2013
DOI: 10.5543/tkda.2013.53059
|View full text |Cite
|
Sign up to set email alerts
|

Our clinical experience of Takotsubo cardiomyopathy and the first case series from Turkey

Abstract: This study presented the first data about TC in Turkey while attempting to increase awareness about the disease. Emergent ventricle evaluation by ventriculography or echocardiography is recommended for acute coronary syndrome patients with non-critical stenosis for the differential diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…For these reasons, it is often misdiagnosed as ST-elevation myocardial infarction (STEMI). The correct diagnosis can be made after further investigations by echocardiography or ventriculography with typical hypokinetic and ballooning visualization of the apex of the left ventricle, performing coronary angiography to show normal flow in the coronary arteries, and detecting the absence of late gadolinum involvement in cardiac magnetic resonance imaging, although it is not found in most clinics [12]. Moderate enzyme elevation was observed in all our cases.…”
Section: Discussionmentioning
confidence: 64%
“…For these reasons, it is often misdiagnosed as ST-elevation myocardial infarction (STEMI). The correct diagnosis can be made after further investigations by echocardiography or ventriculography with typical hypokinetic and ballooning visualization of the apex of the left ventricle, performing coronary angiography to show normal flow in the coronary arteries, and detecting the absence of late gadolinum involvement in cardiac magnetic resonance imaging, although it is not found in most clinics [12]. Moderate enzyme elevation was observed in all our cases.…”
Section: Discussionmentioning
confidence: 64%
“…They suggested that the increase in catecholamine levels may trigger this. Küçükdurmaz et al[ 17 ] also reported that four of six patients returned to normal without complications, and two patients admitted with cardiogenic shock and sudden cardiac death died and received cardiopulmonary resuscitation. Deniz et al[ 18 ] reported TTC, which is usually seen in female patients, in a 92-year-old male patient appeared after the operation for a bladder tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Takotsuba cardiomyopathy is a benign clinical condition characterised by chest pain, elevated ST segment on ECG and elevated cardiac enzymes [31]. It is thought to be stress-related.…”
Section: Takotsuba Cardiomyopathymentioning
confidence: 99%